La Chronica Boemorum y una afirmación del latín - Lavalle, Raúl (Byzantion Nea Hellás, 2006)
The Chronica Boemorum was written by Cosmas Pragensis (1045-1125). It is a very important document to understand the Slavic people‘s history. In this paper we translate and comment a passage. In it Pope John XIII puts the basis of Latin tradition in Bohemia. We add our own feelings about the importance of Latin world, to which the chronicle gave a great contribution.